2002
DOI: 10.1111/j.1552-6569.2002.tb00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Pitfall of Electron Beam Computed Tomography Angiography in Diagnosis of Subclavian Steal Syndrome

Abstract: A patient presented with vertebrobasilar insufficiency during exertion. Vertebral duplex and transcranial Doppler ultrasonography showed reversal of flow in both intracranial and extracranial vertebral and basilar arteries, suggesting bilateral subclavian and vertebrobasilar steal. Electron beam computed tomography angiography (CTA) showed no evidence of subclavian artery stenosis including normal vertebral artery origin on both sides. However, digital subtraction angiography revealed complete occlusion of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Artificial limitations are also present. Ratanakorn et al 15 reported a patient with SS, in which DSA revealed complete occlusion at the origin of both SA, whereas CTA presented no evidence of SA stenosis. The false-negative CTA finding was attributed to inappropriate contrast administration technique and postprocessing method.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial limitations are also present. Ratanakorn et al 15 reported a patient with SS, in which DSA revealed complete occlusion at the origin of both SA, whereas CTA presented no evidence of SA stenosis. The false-negative CTA finding was attributed to inappropriate contrast administration technique and postprocessing method.…”
Section: Discussionmentioning
confidence: 99%